The Power of Women’s Words in K.J. Erben’s Ballads - Маджарова, Таня (Poznańskie Studia Slawistyczne, 2013)
The power of women’s words in K.J. Erben’s balladsdiscusses the author’s literary texts (the collections Písně and Kytice), in which the woman is presented as a permanent character who is in the focus of significant conflict situations and moral problems. Women’s words have a broad spectrum of expression: from the intimate address to oneself, through the prayer, the blessing, the divination, and the imprecation, to the prophecy. Women’s words refer to a peculiar reflection of the collective memory and norm, but at the same time they bring the woman out of her anonymity, individualizing her in her own desires and intentions.